EFEKTIVITAS PENERAPAN ABSENSI FINGER PRINT DALAM MENINGKATKAN KEDISIPLINAN PEGAWAI - Andriani, Novita; Razak, Andi Rosdianti; Hamrun, Hamrun (Universitas Muhammadiyah Makassar, 2024)
This research aims to determine the extent of the effectiveness of implementing finger print attendance in employee discipline. The type of research used is a qualitative research method with a descriptive research type. The results of the research show that: (a) Achievement of the target in implementing finger print attendance has been achieved and has been proven to be effective, this can be seen from the research results and observations of researchers, namely increasing employee discipline from the level of attendance (b) The adaptability of office employees Tondong Tallasa sub-district head, in implementing finger print attendance, is already able and accustomed to doing finger prints (c) Job satisfaction in implementing the finger print attendance system at the Tondong Tallasa sub-district office, namely the impact on job satisfaction and motivating employees (d) Responsibilities of sub-district office employees Tondong Tallasa in carrying out the tasks given has increased,